KAJIAN EMOSIONALISME DAN EGOISME TOKOH DALAM NOVEL PULANG PERGI KARYA TERE LIYE - Andiko, Muhammad; Wahidy, Achmad; Hetilaniar, Hetilaniar (Parataksis: Jurnal Bahasa, Sastra, dan Pembelajaran Bahasa Indonesia, 2022)
The problem of this study is the emotionality and selfishness of the characters in the novel of Tere Liye Pulang. The purpose of this study is to describe the study of emotionality and egoism in literary novels. The method used in this study is a descriptive method. The data source for this study is the novel Pulang Go by Tere Liye published by Sabak Grip Nusantara Jakarta in January 2021. The data collection technique of this study is the documentary technique. The data analysis technique for this study is the content analysis technique. The results of the research and discussion of the novel Tere Liye Pulang Go show the results of the emotional analysis, which includes the emotions of sadness, anger, fear and happiness of the characters Bujang, Salonga, Krestniy Otets, Maria, Natascha and Thomas. And the results of the analysis of egoism include 4 things, namely how a person perceives himself as himself, how a person thinks about himself, how a person evaluates himself, how a person tries to improve himself in various ways. Keywords: Emotionalism Studies, Selfishness, Novel